Alga-chitecture an integration of algae harvesting into the Imus City Hall - Manuel, Romelyn Grace N. (College of Architecture, University of the Philippines Diliman, 2019)
The project focuses on the innovation of a building technology that make use of microalgae as a major component, and its application in architecture - specifically in the Imus City Hall. The building technology takes on the universal problem of rising energy consumption in the world and the depletion of fossil fuels in the future. A building design that can be applied to the Philippine public infrastructure and buildings which can generates their own energy will have a large impact on the total energy consumption. The research assesses the qualities and morphology of algae. The proposed design of the algae harvesting system and the modular unit of the curtain wall makes use of these information. The building cladding system can cultivate different species of microalgae but focuses on Chlorella vulgaris due to efficacy in producing algae biomass with high oil yield. The results provided by this paper will give you an insight of the possibilities of algae when used in architecture in comparison to industrial applications. This paper can only provide insights of the current algae technologies. In comparison to fossil fuels, biofuels are not profitable yet in terms of costs and low harvesting efficiency. That's why we search for new applications as in components in buildings to find new ways to use algae in the build environment.